An Integrated Ultrasonic Membrane An aerobic System (IUMAS) for Palm Oil Mill Effluent (POME) Treatment - Nour, A. H. (Elsevier Ltd, 2017)
Biogas is formed naturally when palm oil mill effluent (POME) decomposes in the absence of oxygen. Unharnessed, this gas is an unwanted, potentially hazardous contributor to global climate change. Biogas is typically composed of 50–75% methane (CH4), 25–45% carbon dioxide (CO2) and trace amounts of other gases. To overcome POME hazardous problems and retain the methane gas, CH4, this research introduces newly designed of an integrated technology of ultrasonic and membrane for a palm oil mill effluent treatment. To fit kinetic study, six steady states were investigated and the results have shown that the mixed liquor volatile suspended solids (MLVSS) ranges from 12,600 to 19,500 mg/l while the mixed liquor suspended solids (MLSS) ranges from 14,700 to 23,800 mg/l. Three kinetic models Monod, Contois and Chen & Hashimoto were used to evaluate the integrated system at organic loading rates ranging from 1 to 15 kg COD/m3.d. The percentage efficiency of COD removal was from 91.6% to 98.5% and hydraulic retention time, HRT from 400 to 9 days. The influent COD concentrations of the POME ranged from 65,600 mg/l to 86,400 mg/l. The integrated technology of IUMAS is a more attractive solution compared to the case when the palm oil mill effluent either ultrasonic or membrane technology individually.